The impacts of climate change on the crude palm oil derivatives market in Malaysia - Cheah, Sin Nee (2019)
Climate change is one of biggest challenges for the agricultural sector in Malaysia. One of the climatic phenomenon is El Nino-Southern Oscillation (ENSO), which has widespread negative influences on crop yields of the main agricultural commodities including the palm oil. Given the importance of palm oil for Malaysian economy is crucial, the monitoring and prediction of ENSO-induced variations in the Malaysian palm oil market are essential for allowing Malaysian governments to manage the associated risks. The formation of ENSO, might triggered a lack of supply and over demand of palm oil due to adverse impact on production, which has strong impact on the futures price of crude palm oil. This research assess the effects of regular and forecasted event of ENSO on Malaysian crude palm oil futures price dynamics using the daily data between January 2009 and September 2019. The ENSO data were collected from Commonwealth Bureau of Meteorology El Nino So Oscillating Index (NINDSOIA) from Bloomberg Terminal and palm oil related data were collected from Bursa Malaysia Derivative Berhad. This study used the Fully Modifies Ordinary Least Squares Method (FMOLS) and Generalized Autoregressive Conditional Heteroskedasticity (GARCH) to examine the influences of ENSO on Malaysian crude palm oil futures price for month 1 to month 15. The findings showed that ENSO event has statistically significant negative relationship with Malaysia futures crude palm oil price. Similarly, open interest volume of crude palm oil futures market showed statistically significant negative relationship, but total traded volume showed positive relationship. Based on the findings, the implications could be profound for commodity traders and for public sector investments in climate forecasting capabilities. The results of the study are of concern to palm oil manufacturers, financial institutions and researchers in the sectors of the environmental and economic growth of the palm oil markets.